CIAP1 promotes proliferation and migration and prevents apoptosis in gallbladder cancer in vitro. Issue 4 (12th April 2019) - Su, Wei; Jiang, Xiaojie; Chen, Mingyuan; Huang, Maotuan; Tang, Nanhong; Wang, Xiaoqian; Li, Xiujin; She, Feifei; Chen, Yanlin
Abstract : Gallbladder cancer (GBC) is a demanding fatal disease with no ideal treatment for inoperable patients. Recent reports have determined TNF-α associated lymphatic metastasis in GBC, while its resistance to TNF-α-killing remains largely unexplored. In this assay, we first found cellular inhibitor of apoptosis (cIAP1) overexpressed in GBC tissues and the roles in promoting the proliferation and migration of GBC in vitro as its homology cIAP2 does. Then how GBC cell survives TNF-α toxicity and TNF-α-induced apoptosis first prevail as follows. The reduction in cIAP1 does not give rise to apoptosis even with the stimulation of TNF-α. Importantly, the loss of cIAP1 enhanced TNF-α/cycloheximide-induced apoptosis in higher activation statuses of Caspase-8, Caspase-3 without the induction of Complex Ⅱ. In response to TNF-α, the reduction in cIAP1 caused the suppression in nuclear factor-κB (NF-κB) pathway and inhibition of transcription of cell death regulator cellular FLICE-like Inhibitory Protein (c-FLIP) instead. To conclude, cIAP1 is an oncological protein abundant in GBC tissues, which enhances proliferation and immigration and blocks TNF-α from apoptosis through NF-κB pathway in vitro .